Implementation of free water protocols in acute care: An observation of practice. (4th March 2022) - Murray, Joanne; Walker, Chelsea; Doeltgen, Sebastian
Abstract: Purpose: Evidence supporting free water protocols (FWP) in acute settings is limited and the potential risks and benefits for acutely ill patients are not well understood. This study aimed to observe how and with whom FWPs are implemented in acute stroke and general medical units. Method: Mixed methods parallel case study design. Medical and nursing records were evaluated for information pertaining to the implementation of the FWP and outcomes for three patients. Semi-structured interviews conducted with three patient-nurse-speech-language pathologist triads focussed on clinical decision-making and barriers and enablers to FWP implementation. Data were analysed descriptively and triangulated across sources. Result: Patients identified as suitable for a FWP had markedly different presentations to those described in the evidence-base and FWP were consequently significantly adapted. Although patients were permitted water, they received and consumed very small amounts. Speech-language pathologists and nurses identified more barriers than enablers to FWP implementation; cognitive impairments, reliance on others and insufficient documentation were perceived as the key barriers, while clear verbal communication was identified as a facilitator. Conclusion: Overall the findings suggest FWP implementation in the acute care setting is hindered by a lack of standardised procedures and current evidence-base that would otherwise inform best practice.